(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Software-Defined Networks (SDN) provide centralized control for programmable routing, yet traditional algorithms like OSPF and ECMP struggle with dynamic traffic patterns, congestion hotspots, and QoS demands in large-scale deployments. This paper conducts a systematic review of machine learning (ML) techniques— including supervised classifiers, reinforcement learning (RL) agents, and graph neural networks (GNNs)— applied to SDN routing and performance optimization, highlighting their roles in traffic classification (up to 99.81% accuracy), predictive KPI forecasting, and adaptive path selection. We propose the Hybrid Causal-RL-GNN (HCRG) framework, which fuses Graph Attention Networks (GAT) for topology-aware state encoding with a causality-enhanced Soft Actor-Critic (SAC) agent to quantify action impacts and maximize a composite reward function balancing latency, packet loss, and throughput. Trained offline on Mininet-emulated NSFNET and Fat-Tree topologies with Ryu controllers, HCRG deploys via OpenFlow for real-time flow rule installation, incorporating hyperparameters like learning rate 0.001 and discount factor 0.99 over 20,000 episodes. Extensive evaluations under normal, congested, and failure scenarios demonstrate HCRG's superiority: 28% latency reduction (22 ms vs. 45 ms baselines), 22% throughput increase (2.2 Gbps), and 35% loss mitigation (1.6%), outperforming ROAR, RouteNet, and ECMP by 15-35% while maintaining <5 ms inference latency at scale. This work advances autonomous SDN traffic engineering, with implications for 5G/6G and edge computing, paving the way for federated extensions in multi-domain environments.